Alginate Lyase from Indonesian Bacillus megaterium S245 Shows Activities Toward Polymannuronate and Polyguluronate - Subaryono Subaryono; Yuwanita Ardilasari; Rosmawaty Peranginangin; Fransisca Rungkat Zakaria; Maggy Thenawidjaja Suhartono (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2016)
Screening of alginate lyase producing bacteria associated with seaweed Sargassum crassifolium was carried out, and isolate S245, identified as Bacillus megaterium S245 was found to produce high alginate lyase activity. This research was conducted to evaluate activity of the alginate lyase enzyme at various pHs, temperatures and substrates. Polymannuronate and polyguluronate were used to evaluate substrate specificities. Alginate lyase activity was assayed by analysis of reducing sugar released using the 3,5 dinitrosalicylic acid (DNS) method. The research showed that the activity of alginate lyase was optimum at pH of 7.0 and  temperature of 45 0C. This enzyme was active for both polymannuronate and polyguluronate susbtrates. The Vmax and Km of this enzyme for polymannuronate and polyguluronate were 200 unit/ml/min and 79.8 mg/ml for polymannuronate substrate and 27.78 unit/ml/min and 13.17 mg/ml for polyguluronate substrate. This enzyme showed unique characteristic in working toward the two substrates.